1997
DOI: 10.1002/hep.510260324
|View full text |Cite
|
Sign up to set email alerts
|

Defects of the respiratory chain in the normal human liver and in cirrhosis during aging

Abstract: cal studies of the respiratory chain complexes in these and Defects of the respiratory chain are a typical feature of mitochondrial diseases and occur also during normal aging other tissues [11][12][13][14][15][16][17] have revealed that aging is an inhomogeneous process at the cellular level leading to randomly diswhere they have been described in postmitotic tissues. The present study addresses the question of defect expression in tributed defects of cytochrome-c-oxidase (complex IV of the respiratory chain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 120 publications
2
39
0
1
Order By: Relevance
“…Age-related defects of the respiratory chain have also been described in other tissues, especially the skeletal muscle including limb, external eye muscles and diaphragm [47,51,54] and also in the heart and the substantia nigra [32,46]. In a recent study similar defects were also found in normal and cirrhotic livers [55].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Age-related defects of the respiratory chain have also been described in other tissues, especially the skeletal muscle including limb, external eye muscles and diaphragm [47,51,54] and also in the heart and the substantia nigra [32,46]. In a recent study similar defects were also found in normal and cirrhotic livers [55].…”
Section: Introductionmentioning
confidence: 78%
“…This is characterized by a decreased respiratory rate for various substrates, a decrease in respiratory control (quotient of ADP-stimulated/unstimulated respiration) and a significant lowering of phosphorylation rate. In earlier investigations we were able to demonstrate that defects of complex III and especially of complex IV were found with increasing frequency during normal ageing of the liver and in cirrhosis, the defect area being significantly larger in cirrhotic than in normal livers [55].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such damage to mitochondrial DNA appears to be heterogeneous in ageing tissues [55]. Whether this damage to individual mtDNA genomes causes the cell to lose mitochondrial function has been a controversial area, although it is known that there are heterogeneous losses of mitochondrial enzyme activities in muscle and liver tissues in aged animals, whilst liver cells removed from old animals show a heterogeneous loss of mitochondrial membrane potential [56][57][58].…”
Section: Phb Proteins and The Ageing Phenotypementioning
confidence: 98%
“…Отмечаются задержка физического и полового развития, ихтиоз с очагами гиперпигментации, вальгусная девиация голеней и высокий свод стопы. Нарушения со стороны эндокринной системы -дефицит гормона роста, гипогонадизм, сахарный диабет, гипопаратиреоз, наруше-ние адреналового обмена [63,66,[72][73][74][75][76][77][78][79][80].…”
Section: к л и н и ч е с к и е п р о я в л е н и я / с и м п т о м ы unclassified